Encyclopedia of world climatology - Oliver, John E. (Dordrecht, The Netherlands : Springer, 2005)
This book covers various main subfields of climatology, supplies information on climates in major continental areas, and explains the intricacies of climatic processes.
Boundary Layer Climatology 168 D.S. Munro Bowen Ratio 178 John E. Oliver Budyko, Mikhail Ivanovich 179 William A. Dando Carbon-14 Dating 181 Claudio Vita-Finzi Centers of Action 182 Robert M. Hordon Central America and the Caribbean, Climate of 183 Michael A. Taylor and Eric J. Alfaro Climate Affairs 189 Michael H. Glantz Climatic Change and Ancient Civilizations 192 Masatoshi Yoshino Climate Change and Global Warming 199 Michael C. MacCracken Climate Change and Human Health 209 Anthony J. McMichael and Rosalie E. Woodruff Climate Change Impacts: Potential Environmental and Societal Consequences 213 Michael C. MacCracken Climate Classification 218 John E. Oliver Climate Comfort Indices 227 Yuk Yee Yan Climate Data Centers 231 Robert Mark Simpson Climate Hazards 233 Jack Hobbs Climate Modeling and Research Centers 243 Robert Mark Simpson Climate Variation: Historical 247 Rhodes W. Fairbridge Climate Variation: Instrumental Data 263 Enric Aguilar, Robert G. Quayle and J. Murray Mitchell Junior Climate Vulnerability 266 Paul Kay Climate Zones 270 John E. Oliver Climatology 272 H.E. Landsberg/J.E. Oliver Climatology, History of 283 David H. Miller Cloud Climatology 289 Joel Norris Coastal Climate 294 R.A. Muller, H.J. Walker, and S.A. Hsu Commerce and Climate 298 David Changnon Condensation 302 John E. Oliver Continental Climate and Continentality 303 Richard Snow Coral Reefs and Climate 305 J. Kleypas Coriolis Effect 306 Yuk Yee Yan Crime and Climate 307 James Lebeau Cultural Climatology 308 John Thornes Cycles and Periodicities 309 W.J. Burroughs Degree Days 315 Danny M. Vaughn Desertification 318 Michael H. Glantz Deserts 324 Sharon E. Nicholson Determinism, Climatic 333 Akhtar H. Siddiqi and John E. Oliver Dew/Dewpoint 336 John E. Oliver Doldrums 338 Joseph Gentilli Drought 338 Donald A. Wilhite Dynamic Climatology 341 Glen A. Marotz Easterly Waves 346 John E. Oliver Ekman (Spiral) Layer 347 Rhodes W. Fairbridge Electromagnetic Radiation 348 Rhodes W. Fairbridge El Nino 349 Michael H. Glantz CONTENTS vi Energy Budget Climatology 351 David Greenland Europe, Climate of 355 Keith Robert Boucher Evaporation 367 W.C. Swinbank Evapotranspiration 370 John E. Oliver Extratropical Cyclones 373 Greg Bierly Ferrel Cell 378 Rhodes W. Fairbridge Flohn, Hermann 379 Cameron Douglas Craig Fog and Mist 379 John A. Day Folklore, Myths and Climate 380 Randall S. Cerveny Frost 381 Benjamin Moulton and John E. Oliver Gentilli, Joseph 384 John Dodson Geomorphology and Climate 385 Susan Berta Global Environmental Change: Impacts 388 R.E. Munn and A.R. Maarouf Greenhouse Effect and Greenhouse Gases 391 A.J. Pitman Hadley Cell 398 John E. Oliver Hadley, George 399 Lisa M. Butler Harrington Hail 399 Lewis G. Wixon Hare, F. Kenneth 402 John Hay Heat Index 403 Thomas W. Schlatter Heat Low 405 L.M. Trapasso Holocene Epoch 405 Neil Roberts Horse Latitudes 406 Rhodes W. Fairbridge Howard, Luke 406 Cameron Douglas Craig Human Health and Climate 407 Laurence S. Kalkstein von Humboldt (Baron), Friedrich Heinrich Alexander 412 Lisa M. Butler Harrington Humid Climates 412 James A. Henry Humidity 413 John E. Oliver and Rhodes W. Fairbridge Hydroclimatology 415 Wayne M. Wendland Hurricanes - Data and Data Sources 420 John E. Oliver Ice Ages 422 Rhodes W. Fairbridge Icebergs and Heinrich Events 424 Rhodes W. Fairbridge Icelandic Low 428 Robert M. Hordon Indian Summer 429 John E. Oliver Intergovernmental Panel in Climate Change (IPCC) 429 John E. Oliver Intertropical Convergence Zone (ITCZ) 429 Yuk Yee Yan Inversion 432 John E. Oliver "ISO" Terms 433 John E. Oliver and Rhodes W. Fairbridge Jet Streams 435 Elmar Reiter and Greg Bierly Katabatic (Gravity) Winds 440 D.S. Munro Kepler's Laws 441 Rhodes W. Fairbridge Koppen, Wladimir Peter 441 William A. Dando Krakatoa Winds 442 Rhodes W. Fairbridge Kyoto Protocol 443 John E. Oliver Lakes, Effects on Climate 444 Thomas W. Schmidlin CONTENTS vii Lamb, Hubert H. 445 Mick Kelly Land and Sea Breezes 446 Yuk Yee Yan Landsberg, Helmut E. 447 Ferdinand Baer Lapse Rate 448 Rhodes W. Fairbridge and John E. Oliver Latent Heat 450 David R. Legates Lightning 451 S. Ladochy Literature and Climate 453 Christina Dando Little Ice Age 457 Rhodes W. Fairbridge Local Climatology 460 Masatoshi Yoshino Local Winds 467 John E. Oliver The Madden-Julian Oscillation (MJO) 476 John E. Oliver Maritime Climate 477 John E. Oliver Mather, John R. 479 Sandra F. Pritchard Mather Maunder, Edward Walter and Maunder Minimum 480 Patrick Moore and John E. Oliver Maury, Matthew Fontaine 481 Lisa M. Butler Harrington Medieval Warm Period or "Little Climatic Optimum" 482 Rhodes W. Fairbridge Mediterranean Climates 485 G. Jay Lennartson Microclimatology 486 W.G. Bailey Middle Latitude Climates 500 Allen Perry Milankovitch, Milutin 502 George Kukla and Rhodes W. Fairbridge Military Affairs and Climate 503 Richard W. Dixon Models, Climatic 505 Brian Hanson and Cort J. Willmott Monsoons and Monsoon Climate 509 S.K. Dash Montreal Protocol 516 John E. Oliver Mountain and Valley Winds 516 John E. Oliver and Rhodes W. Fairbridge Mountain Climates 517 David Greenland National Center for Atmospheric Research 524 Anon National Climate Data Center/Data Sources 524 John E. Oliver North America, Climate of 525 William T. Corcoran and Elias Johnson North American (Canadian) High 535 Robert M. Hordon North Atlantic Oscillation 536 James W. Hurrell Ocean-Atmosphere Interaction 540 G.R. Bigg Ocean Circulation 547 J.G. Harvey and J.E. Oliver Orographic Precipitation 552 Donna Tucker Oscillations 555 John E. Oliver Ozone 556 J. Ben Liley Pacific (Hawaiian) High 562 Robert M. Hordon Pacific North American Oscillation (PNA) 563 John E. Oliver Paleoclimatology 564 A.S. Goudie Palmer Index/Palmer Drought Severity Index 571 James E. Newman and John E. Oliver Phase Changes 573 John E. Oliver Precipitation 574 Donna F. Tucker Precipitation Distribution 576 Orman E. Granger Pressure, Surface 583 Brian D. Giles CONTENTS viii Pressure, Upper Air 588 Brian D. Giles Quasi-Biennial Oscillation 597 Rhodes W. Fairbridge Radar, Climatic Applications 600 David L. Arnold Radiation Climatology 603 Gerald Mills Radiation Laws 611 A. John Arnfield Rainforest Climates 612 John J. Hidore Rainshadow 615 L.M. Trapasso Reanalysis Projects 615 Brian D. Giles Relative Humidity 617 John E. Oliver Religion and Climate 618 William A. Dando Rossby Wave/Rossby Number 625 Jay R. Harman and John E. Oliver Satellite Observations of the Earth's Climate System 629 Graeme L. Stephens Savanna Climate 635 John J. Hidore Scales of Climate 637 A.A.L.N. Sarma Sea Ice and Climate 639 John E. Walsh Sea Level Rise 641 Vivien Gornitz Seasonal Affective Disorder 644 Michael D. Morgan Seasonal Climate Prediction 646 Peitao Peng Seasonality: Astronomic Forcing 648 Rhodes W. Fairbridge Seasons 651 Ted Alsop Sensible Heat 655 David R. Legates Siberian (Asiatic) High 656 Robert M. Hordon Singularities 657 John E. Oliver Snow and Snow Cover 658 Ross D. Brown and David A. Robinson Solar Activity 663 James H. Shirley Solar Constant 666 James H. Shirley Solar Flare 667 James H. Shirley Solar Radiation 667 L.J. Bruce McArthur Solar Wind 673 John E. Oliver South America, Climate of 673 Norys Jiminez and John E. Oliver Southern Oscillation 679 Rhodes W. Fairbridge Sports, Recreation and Climate 682 Steve Stadler Spring Green Wave 684 Mark D. Schwartz Standard Atmosphere 686 John E. Oliver Statistical Climatology 687 Scott M. Robeson Sunspots 694 Rhodes W. Fairbridge Synoptic Climatology 700 Roger G. Barry Taiga Climate 705 Mary Snow Teleconnections 707 Adam Burnett Temperature Distribution 711 L.M. Trapasso Terrestrial Radiation 716 A. John Arnfield Thornthwaite, Charles W. 717 John R. Mather Thunder 718 Richard K. Cook Thunderstorms 719 Rodger A. Brown CONTENTS ix Tornadoes 724 Edward Aguado and James E. Burt Tourism and Climate 730 Allen Perry Trade Winds and the Trade Wind Inversion 731 T.W. Giambelluca Tree-Ring Analysis 732 Harold C. Fritts and James H. Speer Tropical and Equatorial Climates 742 James Henry Tropical Cyclones 750 Jay Hobgood Troposphere 756 K. Dewey Tundra Climate 756 Mary Snow Turbulence and Diffusion 759 Hans A. Panofsky Ultraviolet Radiation 762 A. John Arnfield Units and Conversions 763 John E. Oliver Urban Climatology 766 Anthony J. Brazel and Dale Quatrocchi Vegetation and Climate 780 John R. Mather and Michael J. Brewer Volcanic Eruptions and their Impact on the Earth's Climate 788 S.L. de Silva Vorticity 794 Greg Bierly Walker Circulation 797 John E. Oliver Water Budget Analysis 798 Robert A. Muller and John M. Grymes III Weather 805 John E. Oliver Wind Chill 805 Thomas W. Schlatter Wind Power Climatology 807 Steve Stadler and Tim Hughes Winds and Wind Systems 813 Robert C. Balling Jr. and Randall S. Cerveny Zonal Index 820 John E. Oliver Index of Authors Cited 823 Subject Index 843
Includes bibliographical references and indexes.
Keywords: Climatology -- Encyclopedias; Meteorology -- Encyclopedias